The stabilization mechanism of the pea protein and rutin complex at the gas/liquid interface and its application in low-fat cream - Chunyang Xia; Fangxiao Lou; Shuo Zhang; Tianfu Cheng; Zhaodong Hu; Zengwang Guo; Ping Ma (Food Chemistry: X)
The objective of this study was to substitute partially fat with pea protein isolate (PP)/rutin (Ru) complexes to produce a healthy and stable low-fat whipped cream. Ru enhanced the foam properties of PP. The Ru binding equivalent was the best at a mass ratio of PP/Ru of 64:4, the PP/Ru complexes particle size was the smallest. The synergistic adsorption of Ru reduced the interfacial tension of the complexes and accelerated their diffusion, permeation, and rearrangement at the air/water interface. The results of rheology and Lissajous plots suggested that PP/Ru complexes functioned as an interfacing stabilizer, enhanced the elastic strength of interface film, and improved the stability of foam. PP/Ru complexes as a fat substitute promoted the aggregation of fat globules and the formation of fat globule network structure. When the substitution rate is 10 %, the texture, stability, and microstructure of the sample are nearly identical to those of full-fat cream.